Afro-American Racial Oppression in Paul Laurence Dunbar and Amiri Baraka's Poems - Amar, Dimas Agus; Widjayanti, Ellita Permata (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2021)
This study explores how Afro-American racial oppression is reflected in Black Writers’ poems, Paul Laurence Dunbar and Amiri Baraka. Using a descriptive-analytical method, this study analyzed words, phrases, and clauses indicating Afro-American racial oppression in the ten selected poems of Paul Laurence Dunbar and Amiri Baraka. Roland Barthes’ semiotic was employed to get the interpretation of the signs used in the poems. These interpretations were strengthen by juxtaposing the meaning with socio-cultural context of the poems using Wellek and Warren’s perspective of sociological approach in literature. The result of the study showed that as African American, both Paul Laurence Dunbar and Amiri Baraka portray the experience and feeling of Afro-Americans towards racial oppression in United States of America. Through the use of particular signs in their poems, Dunbar and Baraka speak up about the ill-treatments directed to Afro-Americans as well as the injustice that occurred in United States. Dunbar depicts the life of African American during the Jim-Crow America where the practice of discrimination was spreading like wildfire. Whilst, Baraka portrays the life of Afro-Americans during the 1960s in which Black people remained the target of oppression. The analysis of the ten selected poems showed that despite the fact that Black residents have achieved formal equality through the Civil Right Acts in 1964, significant racial oppression persists. Afro-Americans had to deal with oppression during and after the segregation era. In their poems, Paul Laurence Dunbar and Amiri Baraka also advocate African Americans to establish racial pride within themselves for them have been degraded through racial oppression by White ruling race.